Effects of crop residue managements and tillage practices on variations of soil penetration resistance in sloping farmland of Mollisols - Wang, Yijiao; Qiao, Jinyou; Ji, Wenyi; Sun, Jian; Huo, Dongxu; Liu, Yupeng; Chen, Haitao (International Journal of Agricultural and Biological Engineering, 2022)
Soil penetration resistance (SPR) is one of the major indicators of soil physical properties. Crop residue managements, tillage practices and their interactions exert significant effects on the SPR. However, rare information is available in the sloping farmland of Mollisols. Field experiments were conducted to investigate the variations of the SPR as affected by crop residue managements and tillage practices on the sloping land in Northeast China from 2015 to 2019. The split-plot experiment was arranged with two crop residue managements (removed, REM and retained, RET), and three tillage practices (no tillage, NT; rotary tillage, RT; plow tillage, PT). SPR data in 0-80 cm soil depth was measured at the end of harvest of maize monoculture. Results showed that the two crop residue managements induced significant variations in the SPR at 0-15 cm, 15-30 cm and 0-80 cm soil depths under NT, RT, and PT treatments, respectively. In comparison with RET treatment, the average values of the SPR under REM treatment were 10.9% and 8.9% higher in 45-60 cm and 60-80 cm soil depths, respectively. The average values of the SPR under PT treatment were 12.4% and 14.1% lower in 0-15 cm soil depth, and 23.9% and 10.4% lower in 15-30 cm soil depth than those under NT and RT treatments. However, the average value of the SPR under PT treatment was 11.2% and 22.0% higher in 60-80 cm soil depth than those under NT and RT treatments, respectively. The SPR generally decreased with the slope position declined in the deeper soil depth (except for the NT+RET treatment). The findings from this research can provide a scientific reference for the establishment of rational cultivation and the sustainable development of productivity on the sloping land of Mollisols in cold regions.Keywords: soil penetration resistance, crop residue management, tillage practice, slope position, soil depth, MollisolsDOI: 10.25165/j.ijabe.20221501.6526Citation: Wang Y J, Qiao J Y, Ji W Y, Sun J, Huo D X, Liu Y P, et al. Effects of crop residue managements and tillage practices on variations of soil penetration resistance in sloping farmland of Mollisols. Int J Agric & Biol Eng, 2022; 15(1): 164–171.